Reframing Learning in Madrasah Ibtidaiyah and Primary School Curricula: A Critical Pedagogical Perspective - Waseso, Hendri Purbo; Suyadi; Siti Fatonah; Anggitiyas Sekarinasih (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study critically examines the emerging learning paradigm in the Madrasah Ibtidaiyah (MI) and primary school (SD) curriculum through the lens of critical pedagogy. It focuses on how deep learning, differentiated instruction, project-based learning, holistic assessment, and Graduate Profile Dimensions collectively reposition teachers’ pedagogical roles. Using a descriptive qualitative document-analysis design, the study examined key national curriculum policy documents and relevant scholarly literature through thematic analysis. The findings indicate that the curriculum framework incorporates several principles associated with critical pedagogy, including dialogical learning, critical reflection, student agency, contextual understanding, and social awareness. Learning is therefore positioned not merely as a technical process for delivering content, but as a transformative practice intended to support students’ intellectual, personal, and social development. However, the realization of this transformative potential remains dependent on teachers’ critical pedagogical capacity, sustained professional development, institutional support, and more equitable implementation across urban and rural educational settings. The study concludes that curriculum transformation in MI and SD contexts requires teachers to move beyond their role as policy implementers and become reflective, innovative, and emancipatory educators who can translate curriculum principles into meaningful classroom praxis. These findings contribute to the discussion of how critical pedagogy can strengthen curriculum implementation in Islamic and primary education.